Application of ultrasound technique to evaluate the testicular function and its correlation to the sperm quality after different collection frequency in rams - Montes-Garrido, Rafael; Riesco, Marta F.; Anel-Lopez, Luis; Neila-Montero, Marta; Palacin-Martinez, Cristina; Boixo, Juan Carlos; de Paz, Paulino; Ortega-Ferrusola, Cristina; Hassan, Mohamed A. A.; Anel, Luis; Alvarez, Mercedes (Frontiers in Veterinary Science, 2022)
The frequency of semen collection is a crucial factor to consider in the rams performance inside breeding centers workout. To evaluate this factor, ram Breeding Soundness Evaluation could include sperm quality evaluation and new predictive and non-invasive tools such as ultrasound technique. In this work, an advanced ultrasonography technology, analyzing the testicular volume, echotexture, and vascular function, was used in three different frequencies of semen collection (abstinence frequency, AF; standard frequency, SF; and intensive frequency, IF). Semen samples were cooled (15 ºC, 6h) and evaluated in terms of production, motility, viability, apoptosis, and content of reactive oxygen species. Correlation coefficients were calculated between ultrasonography measurements of echotexture and blood flow and sperm quality parameters. Our results showed an increase in the testicular echotexture when the frequency of semen collection was intensified. Doppler parameters (PSV, RI, PI, TABF) increased (P≤0.05) when the frequency of semen collection was intensified. The sperm motility and functionality decreased in the samples of IF (P≤0.05)., evidencing the frequency of semen collection’s influence. Moreover, moderate positive correlations were established among echotexture and different Doppler parameters with motility parameters in SF. Furthermore, the influence of abstinence days on AI success was analyzed in a field assay. The highest fertility rates were obtained when males had two to five abstinence days. To conclude, frequency of semen collection could be influenced in terms of semen quantity and sperm quality, showing changes in parenchyma echotexture and testicular vascularization. The standard semen collection frequency was the most adequate option. In addition, ultrasonography may be a predictive tool for estimating variations in the sperm quality of donor rams subjected to different frequencies of semen collection in reproduction centers.